2016
DOI: 10.1017/s1368980016003062
|View full text |Cite
|
Sign up to set email alerts
|

Importance of mental performance in parental choice of food for children aged 4–10 years: a study in four European countries

Abstract: Objective: Typically, attention focuses on how nutrition affects physical health. The present study investigated the importance that parents attach to the impact of diet on mental performance when choosing food for their child. Design: Questionnaire. Setting: Four European countries. Subjects: Parents of children aged 4-10 years (n 1574): England (n 397), Germany (n 389), Hungary (n 398) and Spain (n 390). Results: Most parents (80-85 %) considered the effect of food on four elements of mental performance (chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Research on children's dietary trends showed that parents can play a special role given their various, often unparalleled influence over children's eating habits, particularly via meal preparation (e.g. 34 ) and the enforcement of eating rules (35,36) . In this context, it might be not only important which rules parents state but also how they communicate these rules.…”
mentioning
confidence: 99%
“…Research on children's dietary trends showed that parents can play a special role given their various, often unparalleled influence over children's eating habits, particularly via meal preparation (e.g. 34 ) and the enforcement of eating rules (35,36) . In this context, it might be not only important which rules parents state but also how they communicate these rules.…”
mentioning
confidence: 99%